The Relationship of Smartphone Addiction with Sleep Quality, Eating Attitudes, and Obesity - Dolaş, Deniz; Coşkun, Mustafa Nogay; Erdoğan, Ali (Addicta: The Turkish Journal on Addictions, 2025)
We aimed to examine the relationship between smartphone addiction and sleep quality, eating attitudes, and obesity. This research included 407 university students aged 18–30 years who had been using smartphones for at least the last 6 months. The Smartphone Addiction Scale-Short Form, Pittsburgh Sleep Quality Index, and Eating Attitudes Test were administered to all participants along with the Sociodemographic Data Form. Participants’ height and weight were recorded based on self-reports. Smartphone addiction was found in 45.9% of the students. The median value of the Pittsburgh Sleep Quality Index scale was higher in par- ticipants with smartphone addiction than in those without smartphone addiction (p < .001). The absence of chronic physical illness, presence of psychiatric illness, duration of internet use, duration of smartphone use, duration of social media use, poor sleep quality, and poor eating attitudes were found to be associated with smartphone addiction. It can be said that nearly half of the participants may have smartphone addiction and sleep quality is impaired in those with smartphone addiction. Additionally, smartphone addiction is associated with the presence of psychiatric illness, poor sleep quality, and poor eating attitudes, but not with obesity.